A Semiotic Analysis In Bon Jovi Selected Songs - Jahida, Stris Jumiyanti; Katili, Adriansyah A.; Podungge, Rusni (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
Song lyrics as a form of artistic expression that is full of meaning are often used as a tool to convey deep messages that are close to human life. One of the famous rock bands, Bon Jovi is known for its inspiring and meaningful song lyrics. The author's interest in the meanings contained in Bon Jovi's song lyrics, especially in the songs